2006
DOI: 10.1189/jlb.0405179
|View full text |Cite
|
Sign up to set email alerts
|

The Kupffer cell protects against acute lung injury in a rat peritonitis model: role of IL-10

Abstract: The possibility that Kupffer cells (KCs) play key beneficial and deleterious roles in multiple organ injury in sepsis has been discussed. The role of KCs in lung injury in a rat peritonitis model was investigated. Specifically, the involvement of interleukin (IL)-10, which has anti-inflammatory effects, was examined. Rats were given saline or gadolinium chloride (GdCl3), a KC toxicant, 24 h before cecal ligation and puncture (CLP). Survival was assessed for 7 days after CLP. The liver, lung, and serum were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
3
38
1
Order By: Relevance
“…5B). These findings support and extend the work of Emmanuilidis et al (16) and Kono et al (34). In addition, Data are shown as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 81%
“…5B). These findings support and extend the work of Emmanuilidis et al (16) and Kono et al (34). In addition, Data are shown as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 81%
“…IL-10 has been previously identifi ed as an important endogenous anti-infl ammatory cytokine, and it has been hypothesized that the ratio of IL-10 to TNF-α is important in determining the risk for ARDS and its outcome [26]. Many studies have shown that IL-10 levels decrease during infl ammation [27,28]. However, in this study, it was found that the changes in IL-10 levels paralleled the changes in TNF-α in BALF.…”
Section: Discussioncontrasting
confidence: 53%
“…Induction of sepsis (either due to endotoxin administration or CLP) results in the systemic production of IL-10, and blockade of IL-10 during the septic response dramatically enhances sepsis-induced inflammatory cytokine release, tissue injury, and mortality (52,118,223,232). Similarly, IL-10 −/− mice have prolonged inflammation and enhanced lung injury following intrapulmonary challenge with cytotoxic strains of P. aeruginosa, intratracheal LPS administration, or acute pancreatitis (80,217).…”
Section: Interleukin 10mentioning
confidence: 99%
“…IL-10 is produced by a variety of cell types, including macrophages, dendritic cells, NK cells, and T cells, especially regulatory T cells (T reg ) (56,118). Nonmyeloid cell populations also express IL-10, including epithelial cells and tumor cells.…”
Section: Interleukin 10mentioning
confidence: 99%